2002
DOI: 10.1089/108729102760330272
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Social Support and Antiretroviral Adherence Among an Indigent Population in New York City

Abstract: Survey interviews were conducted with a random sample of 50 primarily indigent, African American and Puerto Rican men and women at an outpatient human immunodeficiency virus (HIV) clinic in the Bronx, New York. Analyses revealed a generally high rate of adherence according to self-report data (i.e., on average, participants reported taking 85% of their medications over the last 3 days). However, adherence to the correct number of pills, dosing schedules, and special instructions was more problematic. No sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
123
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(140 citation statements)
references
References 41 publications
13
123
3
1
Order By: Relevance
“…Differences in health care utilization by marital status have been reported previously, 23 and high IPT default rates among the widowed, divorced or separated reported in this study might suggest that people in broken relationships might be less compliant due to a gap in support of close relatives which is fundamental in coping with HIV/AIDS and sustaining compliance. [23][24][25][26] Higher risk in the widowed, separated and divorced group might also be linked to increased household responsibilities which require shouldering workload that could have been shared between two household heads.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in health care utilization by marital status have been reported previously, 23 and high IPT default rates among the widowed, divorced or separated reported in this study might suggest that people in broken relationships might be less compliant due to a gap in support of close relatives which is fundamental in coping with HIV/AIDS and sustaining compliance. [23][24][25][26] Higher risk in the widowed, separated and divorced group might also be linked to increased household responsibilities which require shouldering workload that could have been shared between two household heads.…”
Section: Discussionmentioning
confidence: 99%
“…Highly active antiretroviral therapy (HAART) has dramatically decreased morbidity and mortality and improved the quality of life in persons with HIV infection; however, these benefits of HAART are dependent upon adherence to medication (Hsu et al, 2001;Simoni et al, 2002). Studies have shown that the optimal adherence rate of 95% for HAART is rare (Lewis and Abell, 2002;Read et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the optimal adherence rate of 95% for HAART is rare (Lewis and Abell, 2002;Read et al, 2003). Therefore, researchers have sought to identify factors influencing medication adherence in order to develop interventions to enhance medication adherence (Hsu et al, 2001;Simoni et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations